2020
DOI: 10.1007/978-3-030-50146-4_39
|View full text |Cite
|
Sign up to set email alerts
|

Deep Conformal Prediction for Robust Models

Abstract: Deep networks, like some other learning models, can associate high trust to unreliable predictions. Making these models robust and reliable is therefore essential, especially for critical decisions. This experimental paper shows that the conformal prediction approach brings a convincing solution to this challenge. Conformal prediction consists in predicting a set of classes covering the real class with a user-defined frequency. In the case of atypical examples, the conformal prediction will predict the empty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…While these methods have conceptual appeal, thus far there has been limited empirical evaluation of this general approach for state-of-the-art CNNs. Concretely, the only works that we are aware of that include some evaluation of conformal methods on ImageNet-the gold standard for benchmarking computer vision methods-are Hechtlinger et al (2018), Park et al (2019), Cauchois et al (2020), andMessoudi et al (2020), although in all four cases further experiments are needed to more fully evaluate their operating characteristics for practical deployment.…”
Section: Related Workmentioning
confidence: 99%
“…While these methods have conceptual appeal, thus far there has been limited empirical evaluation of this general approach for state-of-the-art CNNs. Concretely, the only works that we are aware of that include some evaluation of conformal methods on ImageNet-the gold standard for benchmarking computer vision methods-are Hechtlinger et al (2018), Park et al (2019), Cauchois et al (2020), andMessoudi et al (2020), although in all four cases further experiments are needed to more fully evaluate their operating characteristics for practical deployment.…”
Section: Related Workmentioning
confidence: 99%
“…To address these challenges, we explore the use of conformal predictions methods for medical imaging applications. We argue that conformal predictions may better correspond to clinical decision-making intuition and can be easily incorporated into existing models while providing meaningful statistical guarantees (Messoudi, Rousseau, and Destercke 2020). For example, doctors routinely express uncertainty in the form of comparative sets to arrive at a diagnosis i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Conformal prediction is an approach introduced in [54] that allows, for example, a point prediction method to be extended to form confidence sets, guaranteeing that the set contains the true unknown predictor value with some nominal coverage probability. It has been shown that deep learning architectures such as multilayer perceptrons (MLP), convolutional neural networks (CNN), and gated recurrent units (GRU) often improve in their robustness when enhanced by a conformal prediction algorithm [33]. Conformal prediction has been applied to text classification NLP tasks.…”
Section: Introductionmentioning
confidence: 99%